1998
DOI: 10.1074/jbc.273.7.4027
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Sustained c-Jun N-terminal Protein Kinase Activation and Apoptosis Induced by Tumor Necrosis Factor-α in Rat Mesangial Cells

Abstract: Rat mesangial cells are normally resistant to tumor necrosis factor-␣ (TNF-␣)-induced apoptosis. In this report we show that the cells can be made susceptible to the apoptotic effect of TNF-␣ when pretreated with actinomycin D, cycloheximide, or vanadate. c-Jun N-terminal protein kinase (JNK) has been thought to mediate apoptotic processes elicited by some stimuli, but its involvement in TNF-␣-induced apoptosis has been controversial. JNK activation was investigated under conditions where the mesangial cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
153
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(173 citation statements)
references
References 50 publications
18
153
1
1
Order By: Relevance
“…Given our results and evidence that the promoter of g-GCS contains NF-kB and AP-1 binding sites and that TNF induces the expression of g-GCS , it is possible that g-GCS is the critical mediator. Recently, it was reported that TNF-induced apoptosis requires JNK activation, which suggests this is the critical pathway (Guo et al, 1998;Roulston et al, 1998). We, however, show that g-GCS suppresses TNFinduced activation of both JNK and apoptosis.…”
Section: Discussioncontrasting
confidence: 60%
“…Given our results and evidence that the promoter of g-GCS contains NF-kB and AP-1 binding sites and that TNF induces the expression of g-GCS , it is possible that g-GCS is the critical mediator. Recently, it was reported that TNF-induced apoptosis requires JNK activation, which suggests this is the critical pathway (Guo et al, 1998;Roulston et al, 1998). We, however, show that g-GCS suppresses TNFinduced activation of both JNK and apoptosis.…”
Section: Discussioncontrasting
confidence: 60%
“…To ascertain the specificity of GST-p53 for the oligonucleotide probe, competition assays were also performed (lanes 3 and 4). W and M denote unlabeled wild-type and mutant oligonucleotide competitors, respectively because reports have variously stated that vanadate suppresses, 26,27 enhances, [28][29][30] or induces 31 apoptosis. This may be due to differences in the genetic background of the experimental materials, such as the cells' p53 status, and in the apoptotic stimuli used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The redox regulation of caspase activation (59,60) suggests that vesnarinone may suppress caspases through its antioxidant activity. Recently, a role for JNK activation in TNF-induced apoptosis was reported (61)(62)(63). Thus, it is possible that vesnarinone inhibits apoptosis by inhibiting JNK activation.…”
Section: Discussionmentioning
confidence: 99%